2018
DOI: 10.1039/c8dt01754a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical calcium extraction from 1D-Ca3Co2O6

Abstract: The electrochemical oxidation of a transition metal oxide through calcium extraction is achieved for the first time. The 1D framework of Ca3Co2O6 is maintained upon oxidation and the new phase formed exhibits a modulated structure. The process occurs at high potential and is partially reversible, which opens prospects for a calcium battery proof-of-concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…Specific battery technologies are depicted with symbols, while the hypothetical CaBs are represented by the straight lines with energy densities as a function of the operating voltage and the specific capacity of the cathodes—the capacities are specified on each line. Two specific CaBs have also been considered in more detail: using TiS 2 and Ca 3 Co 2 O 6 as cathode materials, both were shown to be electrochemically active at 100°C (Tchitchekova et al, 2018a,b), although full reversibility and cyclability remain to be demonstrated. The hypothetical Ca-ion technology enlists Ca 3 Co 2 O 6 as the cathode and a graphite anode.…”
Section: Resultsmentioning
confidence: 99%
“…Specific battery technologies are depicted with symbols, while the hypothetical CaBs are represented by the straight lines with energy densities as a function of the operating voltage and the specific capacity of the cathodes—the capacities are specified on each line. Two specific CaBs have also been considered in more detail: using TiS 2 and Ca 3 Co 2 O 6 as cathode materials, both were shown to be electrochemically active at 100°C (Tchitchekova et al, 2018a,b), although full reversibility and cyclability remain to be demonstrated. The hypothetical Ca-ion technology enlists Ca 3 Co 2 O 6 as the cathode and a graphite anode.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical composition, volume and concentration of the electrolyte also have a major influence on reliable application of the RE. Furthermore, emerging battery chemistries, such as Li-S [174], Na-ion [129,[175][176][177], Mg-ion [177,178], Ca-ion [177,179], and Na-O 2 [180], have also considered the use of REs for enhanced electrochemical characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel experimental and computational investigations establish a link between the lack of reversible electrochemical activity (experimentally observed) and hampered Ca diffusion (computationally estimated). [15][16][17][18][19][20] In this regard, the poor diffusion of Ca 2+ in inorganic structures is the major challenge for cathode discovery. 21 Compared to Li + diffusion, the hindrance to Ca mobility resides in the larger size of Ca 2+ ions on one hand and its divalent charge on the other that increases the electrostatic repulsion/attraction with the neighbouring cations/ anions in the structure.…”
Section: Introductionmentioning
confidence: 99%